2018
DOI: 10.3390/ani8030036
|View full text |Cite
|
Sign up to set email alerts
|

Factors Informing Outcomes for Older Cats and Dogs in Animal Shelters

Abstract: Simple SummaryHistorically, older cats and dogs have been particularly at-risk for euthanasia in animal shelters due to their lower perceived appeal for adoption. This study found that the condition at intake had the greatest impact on the outcomes of older cats and dogs. Additionally, the application of specialized veterinary care, such as orthopedic surgery or chronic disease maintenance, is discussed as factors that inform higher rates of live outcomes for these senior companion animals. These findings demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…We also found that dogs' length of stay in foster care was related to their age, such that as age increased, so did time in foster care. While this relationship has been observed with dogs awaiting adoption in the shelter ( 50 , 51 ), this adopter preference for younger dogs in foster care has not been previously characterized.…”
Section: Discussionmentioning
confidence: 82%
“…We also found that dogs' length of stay in foster care was related to their age, such that as age increased, so did time in foster care. While this relationship has been observed with dogs awaiting adoption in the shelter ( 50 , 51 ), this adopter preference for younger dogs in foster care has not been previously characterized.…”
Section: Discussionmentioning
confidence: 82%
“…One study found that dogs 8 years or older are "marginally" more likely to be adopted compared to 5-7 year old dogs [10]. Another study found that when only analyzing geriatric dogs, their average LOS was 89 days, but that health condition was the most predictive factor for adoption [28]. Our findings indicate that the longer senior dogs remain in the shelter, the more adoptable they become relative to other age groups with the same LOS.…”
Section: Discussionmentioning
confidence: 55%
“…This stands in contrast to the modest change documented between 2018 and 2019, when euthanasia decreased by 9%. The literature indicates that these best practices for reducing shelter euthanasia include providing specialized medical and behavior care for animals in shelter care, reducing barriers to adoption (e.g., eliminating adoption fees), engaging in triage and appointment-based admissions, and increasing stakeholder engagement in shelter services (e.g., foster caregiving, partnerships with local private practice veterinarians) ( 35 39 ). Future research should continue to assess which populations of animals are most likely to be euthanized and continue to evaluate which programs are most effective at reducing non-live outcomes in animal shelters.…”
Section: Discussionmentioning
confidence: 99%